2019
DOI: 10.17511/jopm.2019.i11.02
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of central nervous system lesions

Abstract: Introduction: Central nervous system (CNS) neoplasms, in India, constitute 1.9% of all cancers and in U.S. adults-2% of all cancers. Many of the non-neoplastic CNS lesions can clinically & radiologically simulate brain tumours. In such cases, histopathological examination (HPE) can be helpful in differentiating between neoplastic and non-neoplastic etiologies. Materials and Methods: This retrospective descriptive study of histopathological analysis of brain tumours was carried out in TMMC&RC, Department of Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
5
8
0
Order By: Relevance
“…1,9,11,14,15 250 cases (96%) were of primary tumour and 11 cases (4%) were of metastatic deposits. These findings were in agreement with studies by Hema et 2,6,11,12,14,16,17,20,22 Out of 261 neoplastic ICSOLs, majority belonged to gliomas (48%) followed by meningiomas (20%) and schwannomas (9%). (Table 4 2,9,11,14,15,17,20,23 In case of meningiomas our findings were in agreement with studies by Khonglah et 11,12,[14][15][16]18,23 Studies by Pachori et al (42.8%) and Kaki RR et al (32%) reported higher percentage of meningiomas.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…1,9,11,14,15 250 cases (96%) were of primary tumour and 11 cases (4%) were of metastatic deposits. These findings were in agreement with studies by Hema et 2,6,11,12,14,16,17,20,22 Out of 261 neoplastic ICSOLs, majority belonged to gliomas (48%) followed by meningiomas (20%) and schwannomas (9%). (Table 4 2,9,11,14,15,17,20,23 In case of meningiomas our findings were in agreement with studies by Khonglah et 11,12,[14][15][16]18,23 Studies by Pachori et al (42.8%) and Kaki RR et al (32%) reported higher percentage of meningiomas.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were in agreement with studies by Hema et 2,6,11,12,14,16,17,20,22 Out of 261 neoplastic ICSOLs, majority belonged to gliomas (48%) followed by meningiomas (20%) and schwannomas (9%). (Table 4 2,9,11,14,15,17,20,23 In case of meningiomas our findings were in agreement with studies by Khonglah et 11,12,[14][15][16]18,23 Studies by Pachori et al (42.8%) and Kaki RR et al (32%) reported higher percentage of meningiomas. 10,17 Studies by Hema et al (14%), Butt et al (12%), Adnan et al (8.6%), Kaki RR et al (6%), Datta et al (6.5%), Lakshmi et al (5.5%) and Kothari et al (6%) showed similar distribution of schwannomas as in present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations